The effect of government responsiveness on future political participat ion - Mellon, Andrew Jonathan; Sjoberg, Fredrik Matias; Peixoto, Tiago Carneiro (The World Bank, 2015)
What effect does government responsiveness have on political participa tion? Since the 1940s political scientists have used attitudinal measu res of perceived efficacy to explain participation. More recent work h as focused on underlying genetic factors that condition citizen engage ment. The authors develop a ‘calculus of participation’ that incorpora tes objective efficacy, the extent to which an individual’s participat ion actually has an impact, and test the model against behavioral data from FixMyStreet.com (n=399,364). The authors find that a successful first experience using FixMyStreet.com (e.g., reporting a pothole and having it fixed) is associated with a 54 percent increase in the proba bility of an individual submitting a second report. The authors also s how that the experience of government responsiveness to the first repo rt submitted has predictive power over all future report submissions. The findings highlight the importance of government responsiveness for fostering an active citizenry, while demonstrating the value of incid entally collected data to examine participatory behavior at the indivi dual level.